Therapeutic potential of medicinal plants for the management of urinary tract infection: A systematic review. (22nd April 2019) - Shaheen, Ghazala; Akram, Muhammad; Jabeen, Farhat; Ali Shah, Syed Muhammad; Munir, Naveed; Daniyal, Muhammad; Riaz, Muhammad; Tahir, Imtiaz Mahmood; Ghauri, Aymen Owais; Sultana, Sabira; Zainab, Rida; Khan, Muslim
Abstract: Urinary tract infection (UTI) is one of the most severe public health problem affecting both sexes but females are more susceptible due to the differences in urogenital and reproductive anatomy, physiology and lifestyle. As in UTI, different parts of the urinary tract are affected and morbidity due to UTI is more common in women of all ages and older men. Due to multi‐drug resistant strains and high recurrence rate, UTI has become a major socioeconomic burden. The current review article was aimed to describe the natural therapeutic strategies to manage and cure the UTI. For this purpose, different databases including Google Scholar, Cochrane database, and PubMed etc. were explored. Inclusion criteria were any research article investigating the current therapy of UTI. It was found that microbial infections including Escherichia coli, Enterococcus faecalis and Klebsiella species are the major causes of UTI with different signs and symptoms including painful urination or dysuria, hematuria, urinary urgency, burning micturition, frequent urination, nausea, and vomiting. Antibiotics like trimethoprim, sulfamethoxazole, quinolone etc. as the first choice of the drug are used worldwide. However, due to microbial resistance, several life‐threatening side effects, repeated high doses, high cost and low efficacy of these antibiotics motivated the researchers to explore natural remedies for the treatment of UTI. Herbal medicines are effective to combat bacterial resistance with high efficacy, and easy availability with minimal or no side effects. For these reasons it has attained the attention of researchers wanting to explore the herbal treatment of UTI. Vaccinium macrocarpon, Tribulus terrestris, Trachyspermum copticum, Cinnamomum verum and Hybanthusenn easpermus are some common medicinal plants reported to have therapeutic potential for the management and cure of the UTI. Although herbal medicines have more potential over conventional medicine but more discoveries are required to explore the phytoconstituents and their mechanism of action responsible for the management and cure of UTI.